2014
DOI: 10.1186/s40691-014-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Firefighters’ needs for personal protective equipment

Abstract: This study performed focus group interviews with 54 firefighters in four states in the United States to assess the needs for design of firefighters' personal protective equipment. Firefighters' responses indicate three major issues to be considered for improved mobility, comfort and safety: 1) consideration of human factors, 2) sizing and fit, and 3) integrity of protection in the interface between protective equipment and turnout ensemble. Ergonomic design issues were identified through firefighters' response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 12 publications
1
57
0
2
Order By: Relevance
“…In 1981, the NFPA required US firefighters to wear personal protective equipment (PPE) and SCBA. 38 Although the use of respiratory protection has become standard in the fire service, certainly in large career fire departments, the systematic use of SCBAs is arguably more important now than when first introduced due to the increasing toxicity of smoke in modern fires. 39 Unfortunately, there may be inconsistent and inadequate use of respiratory protection in the fire service.…”
Section: Discussionmentioning
confidence: 99%
“…In 1981, the NFPA required US firefighters to wear personal protective equipment (PPE) and SCBA. 38 Although the use of respiratory protection has become standard in the fire service, certainly in large career fire departments, the systematic use of SCBAs is arguably more important now than when first introduced due to the increasing toxicity of smoke in modern fires. 39 Unfortunately, there may be inconsistent and inadequate use of respiratory protection in the fire service.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several researchers (Park & Hahn, 2014; Park, Hur, Rosengren, Horn, & Hsiao-Wecksler, 2010; Park, Kim, et al, 2015; Park, Park, Lin, & Boorady, 2014; Park, Trejo, et al, 2015) have recently indicated, through a series of biomechanical tests with firefighters, that SCBA and fire boots are the two major contributors to musculoskeletal fireground injuries (e.g., lower back pain, trips, slips, and falls) that result in loss of work as well as increased medical costs. Park, Kim, et al (2015) showed that wearing inflexible fire boots significantly restricts firefighters’ natural foot pronation, alters gait, and slows down their response time as they negotiate with the fireground.…”
mentioning
confidence: 99%
“…Heavy weight, inferior ventilation, and bulky nature makes it a burden for firefighters. Reproduced with permission . Copyright 2014, Springer Nature.…”
Section: Limitations Of Currently Used Personal Protective Equipment mentioning
confidence: 99%